The effect of servicescape on employees' performance at PKT Logistics (M) Sdn Bhd, 2008 / Nur Ayzan Mohd Youssof - Mohd Youssof, Nur Ayzan (Faculty of Business and Management, 2008)
Positive servicescape has been identified as a driver of performance. It is important because employees' valuations of the servicescape will influence their job performance. Nowadays, numbers of civil servants that suffer from workplace situation have increase. So that it is important for management to manage their servicescape and improve weaken area. This study is a research of "The Effect of Servicescape on Employees' Performance at PKT logistics (M) Sdn Bhd". The study utilize questionnaire as the instrument for collecting data. Questionnaires have been distributed to 33 employees from all departments at the organization to do the research. In this study, researcher has identifying the factor of servicescape at PKT logistics (M) Sdn Bhd and the level of job performance of the employees. Researcher will have used the Statistical Package for Social Science (SPSS) Program Student Version. From the analysis researcher have identify that there is significant relationship between servicescape and performance of employees at PKT logistics (M) Sdn Bhd.